Low dose of flurochloridone affected reproductive system of male rats but not fertility and early embryonic development - Rui Li; Su Zhou; Hongyan Zhu; Zhichao Zhang; Jing Fang; Ping Liu; Yu Wang; Xiuli Chang; Yubin Zhang; Liming Tang; Zhijun Zhou (BMC, 2019)
Abstract Background Fluorochloridone (FLC) is a widely used herbicide, and its target organs are testes and epididymides. The Globally Harmonized System of Classification and Labelling of Chemicals classified FLC as Level 2-possibly cause fertility or fetal damage (no relevant data support). The maximum residue levels of FLC in processed crops have been reviewed in the latest European Food Safety Authority (EFSA) report in 2018. However, the toxic effect of FLC on fertility and early embryonic development is limited, and the health risk assessment of FLC needs further consideration. This study investigated the potential effects of FLC on fertility and early embryonic development in rats. Methods One hundred rats of each sex were divided into four groups including three FLC-treated groups at doses of 2 mg/kg, 5 mg/kg and 15 mg/kg, and a vehicle control group (0.5% (w/v) sodium carboxymethyl cellulose). Male and female rats were dosed for 9 and 2 consecutive weeks, intragastrically, prior to cohabitation and lasted throughout the mating period for males and continued until Gestation Day 7 (GD7) for females. Parameters such as weights and coefficients of reproductive organs, epididymal sperm number and motility, indexes of copulation, fecundity and fertility indexes, mating period, estrous cycle, corporalutea number, implantations, live, dead and resorbed fetuses, preimplantation loss rate, and postimplantation loss rate were observed in this study. Results Obvious toxicity of male reproductive system was found at the dose of 15 mg/kg including decreases in testicular and epididymal weight, also in sperm motility rate. Whereas the increase in sperm abnormality rate was observed. However, no significant effects of FLC were found on lutea count, implantations count, fetuses count and weight, live fetuses count (rate), dead fetuses count (rate), resorbed fetuses count (rate), placentas weight, fetuses gender, preimplantation loss (rate) and postimplantation loss (rate). Furthermore, FLC had no adverse effects on fertility and early embryonic development in rats. Conclusion The no-observable-adverse-effect level (NOAEL) of FLC on fertility and early embryonic development in rats was considered to be 5 mg/kg/day.